Experimental study of the impacts of cold mass fraction on internal parameters of a vortex tube. (August 2019) - Li, Nian; Jiang, Guannan; Fu, Lichen; Tang, Liming; Chen, Guangming
Highlights: A five-hole probe and several thermocouples were used to obtain the internal parameters of a large vortex tube. Four different cold mass fraction conditions (0.2, 0.4, 0.6 and 0.8) were chosen. The 3-D velocities were presented, and the tangential velocity was considered to be the steady Burgers vortex form. The pressure and temperature inside the vortex tube were presented and discussed. Abstract: In order to get the internal parameters of a vortex tube, a large-scale vortex tube was designed and an experimental device was built. A five-hole probe and thermocouples were used to obtain the three-dimensional velocities, the static pressure, static temperature and total temperature distributions inside the vortex tube. Four different cold mass fraction conditions (0.2, 0.4, 0.6 and 0.8) were chosen and the impacts on the internal parameters of the vortex tube were discussed. Different from the traditional view, the tangential velocity was considered to be the steady Burgers vortex form. A reverse flow boundary was found, and the location of which was changed at different operation conditions and axial positions. Further, it was found that the lowest static temperature existed near the nozzle outlet, and a new static temperature difference distribution law was firstly proposed experimentally.